Whole-of-community and intersectoral interventions that address alcohol-related harms: A scoping review - Ulla Walmisley; Michelle De Jong; Asha George; Ida Okeyo; Carmen Späth; Nandi Siegfried; Nadine Harker; Mark Tomlinson; Tanya Doherty (Global Public Health)
Alcohol harms threaten global population health, with youth particularly vulnerable. Low – and middle-income countries (LMIC) are increasingly targeted by the alcohol industry. Intersectoral and whole-of-community actions are recommended to combat alcohol harms, but there is insufficient global evidence synthesis and research examining interventions in LMIC. This paper maps existing literature on whole-of – community and intersectoral alcohol harms reduction interventions in high-income countries (HIC) and LMIC. Systematic searching and screening produced 61 articles from an initial set of 1325: HIC (n = 53), LMIC (n = 8). Data were extracted on geographic location, intersectoral action, reported outcomes, barriers, and enablers. HIC interventions most often targeted adolescents and combined community action with other components. LMIC interventions did not target adolescents or use policy, schools, alcohol outlets, or enforcement components. Programme enablers were a clear intervention focus with high political support and local level leadership, locally appropriate plans, high community motivation, community action and specific strategies for parents. Challenges were sustainability, complexity of interventions, managing participant expectations and difficulty engaging multiple sectors. A learning agenda to pilot, scale and sustain whole-of-community approaches to address alcohol harms in settings is crucial, with consideration of local contexts and capacities, more standardised methods, and a focus on community-driven action.